ITIH4: A New Potential Biomarker of "Toxin Syndrome" in Coronary Heart Disease Patient Identified with Proteomic Method. (19th August 2013) - Xu, Hao; Shang, Qinghua; Chen, Hao; Du, Jianpeng; Wen, Jianyan; Li, Geng; Shi, Dazhuo; Chen, Keji
Abstract : Objective . This trial aims to look for the protein biomarker of "toxin syndrome" of CHD patients. Methods . We have performed two trials in this paper. The first trial was a randomized controlled trial (RCT) of the plasma proteome in unstable angina (UA) patients by Maldi-Tof Mass. The second trial was a nested case-control study in 1503 stable CHD patients with one-year followup for acute cardiovascular events (ACEs). Results . In the RCT study, 12 protein spots were found to be the differential protein for the significant differences between the difference of before and after treatment in group A and group B; 2 of them (3207.37 Da and 4279.95 Da) was considered to be unique to "toxin syndrome" for being differential proteins of group B but not group A. These 2 spots were identified as Isoform 1 of Fibrinogen alpha chain precursor (FGA, 3207.37 Da) and Isoform 2 of inter-alpha-trypsin inhibitor heavy chain H4 (ITIH4, 4279.95 Da), respectively. In the nested case-control study, the result of Western blot demonstrated that protein expression of ITIH4 in the group with followup ACEs was significantly lower than the matched group without followup ACEs (P = 0.027 ). Conclusion . ITIH4 might be a new potential biomarker of CHD "toxin syndrome" in TCM, indicating the potential role in early identifying high-risk CHD patients in stable period.